(untitled) (Gaceta Técnica, 2015)
In the present review of the book of Professor Tushar Kanti Datta, of the Indian Institute of Technology, Delhi, the most relevant appraisals are collected, in order to provide guides for those interested in the subject of the dynamics of structures, both at the undergraduate level of postgraduate although the book has been published in 2010, the subject matter is of particular interest, due to the proposal to incorporate the subject Seismic Analysis to the Civil Engineering curriculum of the Lisandro Alvarado Centroccidental University (UCLA) Barquisimeto, Venezuela